2023
DOI: 10.1002/lno.12350
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid carbon isotope fingerprints are unique among eukaryotic microalgal taxonomic groups

Abstract: Eukaryotic microalgae play critical roles in the structure and function of marine food webs. The contribution of microalgae to food webs can be tracked using compound-specific isotope analysis of amino acids (CSIA-AA). Previous CSIA-AA studies have defined eukaryotic microalgae as a single functional group in food web mixing models, despite their vast taxonomic and ecological diversity. Using controlled cultures, this work characterizes the amino acid δ 13 C (δ 13 C AA ) fingerprints-a multivariate metric of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…1). While environmental gradients may also specifically modify the fractionations associated with each AA synthesis pathway, these relative differences will likely be very small compared to the overall average effect of the environment on physiology, and therefore carbon acquisition (Stahl et al 2023, Larsen et al 2015, Fig. 2), represented here as Env.…”
Section: Conceptualising Amino Acid δ 13 C Valuesmentioning
confidence: 99%
See 3 more Smart Citations
“…1). While environmental gradients may also specifically modify the fractionations associated with each AA synthesis pathway, these relative differences will likely be very small compared to the overall average effect of the environment on physiology, and therefore carbon acquisition (Stahl et al 2023, Larsen et al 2015, Fig. 2), represented here as Env.…”
Section: Conceptualising Amino Acid δ 13 C Valuesmentioning
confidence: 99%
“…In some studies, even finer distinctions in δ 13 C-EAA pattern distinctions have been observed between organs of individual plants, i.e. roots, seeds, and leaves (Lynch et al 2011 as well as among marine phytoplankton clades (Larsen et al 2020, Stahl et al 2023. Based on the available evidence, separation in δ 13 C-EAA patterns can be attributed to both phylogeny and phenotypic factors (section 2.2).…”
Section: The Diagnostic Potential Of δ 13 C-eaa Patterns Among Basal ...mentioning
confidence: 99%
See 2 more Smart Citations
“…These regional changes in phytoplankton dynamics coincide with observed changes in krill and penguin populations (Montes-Hugo et al 2009). Future work using δ 13 C CSIA-AA fingerprinting (Stahl et al 2023) could help reconstructing changes in plankton community composition to explore this plankton community-driven food chain length hypothesis.…”
Section: Factors Influencing Adélie Penguin Trophic Positionmentioning
confidence: 99%